STUDY OF COMMUNITY PERCEPTIONS OF THE DEVELOPMENT OF KENDAL INDUSTRIAL AREA, CENTRAL JAVA PROVINCE - Salsabila Laili Lam'aa' Sania; Ali Zainal Abidin (SEAN Institute, 2023)
The measure of a country's economic growth can be seen from its level of productivity. With development, it can utilize the resources and potential in each region that can support development. One of the economic sectors that can contribute to the economic development process is the industrial sector. One of the areas that is experiencing industrial growth is Kendal Regency with the Kendal Industrial Estate (KIK). This study aims to analyze the characteristics of the impact of the development of the Kendal Industrial Estate on the people of Wonorejo Village and Brangsong Village, Kendal Regency. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. For data analysis, this research uses analysis through data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed that: 1) The community welcomes the development of Kendal Industrial Estate (KIK); 2) The surrounding community feels the positive impact felt by the existence of industrial development, namely being able to open job vacancies for the community around the industrial area, reduce unemployment, lift the village economy, the surrounding community can also sell or open boarding houses for workers in the Kendal Industrial Estate who are immigrants. While the negative impacts felt by the surrounding community are frequent flooding during the rainy season, air pollution, the environment feels more arid due to many dead trees.